1996
DOI: 10.1007/bf00203902
|View full text |Cite
|
Sign up to set email alerts
|

Metal accumulation in a biological indicator (Ulva rigida) from the lagoon of Venice (Italy)

Abstract: Ulva rigida (C. Agardht) was collected from the Palude della Rosa (lagoon of Venice), a particular area characterized by a salinity gradient, from December 1991 to June 1993. Metal contents (Al, Mn, Fe, Cu, Zn, Cr, Co, Ni, Cd, and Pb) were determined by atomic absorption spectrophotometry and statistically analysed for differences between months and sampling sites. The mean seasonal variability is very significant (p < 0.001) for all studied metals. Seasonal trends are comparable for groups of metals according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 51 publications
(66 reference statements)
3
31
0
1
Order By: Relevance
“…Furthermore, the results from an experimental study indicated that Cu accumulation by U. reticulata at salinity of 20 psu was three times higher than that at 35 psu (Mamboya et al 2009). Similar results were published for two cosmopolitan Ulva species, where the accumulation of Zn and Cd in U. rigida and Cr and Zn in U. lactuca increased along with the decreasing salinity (Favero et al 1996). In the experimental studies it was observed that reducing the salinity of the medium increases the amount of Cu ions accumulated by Ulva reticulata thalli (Mamboya et al 2009).…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, the results from an experimental study indicated that Cu accumulation by U. reticulata at salinity of 20 psu was three times higher than that at 35 psu (Mamboya et al 2009). Similar results were published for two cosmopolitan Ulva species, where the accumulation of Zn and Cd in U. rigida and Cr and Zn in U. lactuca increased along with the decreasing salinity (Favero et al 1996). In the experimental studies it was observed that reducing the salinity of the medium increases the amount of Cu ions accumulated by Ulva reticulata thalli (Mamboya et al 2009).…”
Section: Discussionsupporting
confidence: 76%
“…Also, for U. compressa from the Gulf of Aden, the order of metal concentrations was: Ni > Pb > Cd (Al-Shwafi and Rushdi, 2008). The order of heavy metal concentrations, for marine species such as U. rigida from the Lagoon Venice or U. compressa (Favero et al, 1996), correlated closely with the order observed for freshwater Ulva. Moreover, Cd had the lowest concentrations for both thalli from marine and freshwater Ulva species.…”
supporting
confidence: 53%
“…the following trend: Ni > Pb > Cd (Favero et al, 1996). Also, for U. compressa from the Gulf of Aden, the order of metal concentrations was: Ni > Pb > Cd (Al-Shwafi and Rushdi, 2008).…”
mentioning
confidence: 89%
“…Bragato et al (2006) monitored growth dynamics, nutrient and heavy metal accumulation in the two dominating macrophytes Phragmites australis and Bolboschoenus maritimus, but they found that the heavy metal concentration in water and soil was not correlated to the plant content. Favero et al (1996) investigated the metal accumulation of Ulva rigida and reported that this specie specifically accumulates Fe. Caliceti et al (2002) measured the concentrations of heavy metals (Fe, Zn, Cu, Cd, Ni, Pb, Cr, As) in seven seaweeds of environmental and commercial relevance.…”
Section: Effects Of Pollution On Organismsmentioning
confidence: 99%